Concordance Between Endoscopic Diagnosis of Laryngeal Lesions and Pathology Results - ابراهيم, مصطفى; يوسف, يوسف; عجوب, اليسار (Latakia University Journal -Medical Sciences Series, 2020)
Objectives: Assessment of concordance between endoscopic diagnosis of laryngeal lesions and pathology results. Study design: Analytical Study (Cross Sectional) Patients and methods: 100 patients with laryngeal lesions (70 males and 30 females) We included all patients who underwent microsurgery of the larynx, whose videolaryngoscopic tests showed vocal fold lesions, from January 2018 January2020. A correlation between histopathological findings and clinical hypothesis of laryngeal lesions was performed. Results: there was agreement in 80% of cases between the clinical and pathological diagnosis. Conclusions: Our study showed that the clinical videolaryngoscopic diagnosis does not always correlate with the pathological diagnosis